Program Pembiayaan Usaha Syariah (Pusyar) PT BPR Syariah Kota Mojokerto untuk Inklusi Keuangan UMKM - Wahyuningsari, Wahyuningsari; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study uses a descriptive qualitative approach. This purpose of this research is determine the achievement of financial inclusion indicators from the implementation Pusyar. Data collection techniques in this study were interviews, observation and documentation. The results is Pusyar as a public policy that successfully maximizes the achievement of three indicators of financial inclusion. Access, usage and quality. Although, welfare is the fourth indicator, it has not been maximally achieved from this program. Pusyar is an example of the realization of public policy in accordance with the concept of Socio-Economic and Financial Restructure. Which this policy optimizes Islamic philanthropy in Islamic financial products to develop SMEs. in the end the policy resulted in the achievement of financial inclusion proces.